Sabar dalam Perspektif Surah Al Baqarah Ayat 153 - Muda HSB, Mahmud; Meriyon; M. Muzzaki Pratama; Edi Hermanto (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to examine the meaning and urgency of patience (ṣabr) in QS. Al-Baqarah verse 153 and its relevance to the life of a Muslim, particularly in the context of modern life. This research employs a qualitative approach using a library research method, with data sources consisting of the Qur’an, classical and contemporary Qur’anic commentaries, as well as relevant supporting literature. Data analysis was conducted through descriptive-analytical analysis of scholars’ interpretations related to the concept of patience. The results indicate that patience in QS. Al-Baqarah:153 is not merely a passive attitude of self-restraint, but an active disposition that encompasses perseverance in obedience to Allah, restraint from sinful acts, and steadfastness in facing divine decree. Patience is positioned as a means of attaining Allah’s assistance, a form of special closeness with Allah (ma‘iyyah), and a foundation for the spiritual resilience of a believer. Moreover, patience functions as a pillar of success in both worldly and hereafter life and demonstrates strong relevance to modern life in psychological, educational, social, and professional aspects. Thus, patience constitutes a fundamental value that must be internalized as a guiding principle in a Muslim’s life in order to face contemporary challenges with steadfast faith and inner balance.